Nova’s Film: Notes on a Toddler’s iPhone Movie - Bem, Caroline (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2025)
A toddler, not quite two years old, records a 7’ 46” iPhone video. This “perfect” film (after Jørgen Leth’s “perfect” human) exposes the basic operations of smartphone thinking-feeling (Massumi). Drawing on haptic theories of filmic engagement (Marks, Sobchack), I examine how Nova’s camera returns, again and again, to rugs, throws, windows, chairs, and to the hardwood floor. Adult voices—mother, father, grandmother—provide a mundane soundtrack which offsets Nova’s systematic inquiry into medial visual perception. At the film’s center, a brief, surprisingly steady shot gathers the adults at the kitchen counter into a domestic “primal scene” that allows the child to come to terms with both closeness and distance: rather than simply tethering (Turkle) Nova to her parents, the phone works like a small “holding” device, in a Winnicottian sense. Finally, as Nova’s grandmother directs her to “take a picture of my flowers,” and before the phone is wrested from her, it becomes evident that Nova has developed a true method for seeing-being in the world.